Applications in basic marketing : clippings from the popular business press - McCarthy, E. Jerome (Edmund Jerome); Perreault, William D.; McCarthy, E. Jerome (Edmund Jerome); McCarthy, E. Jerome (Edmund Jerome) (Irwin, 2000)
"Clippings from the popular business press."